2014
DOI: 10.14419/ijasp.v2i2.3373
|View full text |Cite
|
Sign up to set email alerts
|

Weibull-Bayesian analysis based on ranked set sampling

Abstract: Most of estimation methods reported in the literature are based on simple random sampling (SRS), which to certain extent is considerably less effective in estimating the parameters as compared to a new sampling technique, ranked set sampling (RSS) and its modifications. In this Paper we address the problem of Bayesian estimation of the parameters for Weibull distribution, based on ranked set sampling. Two loss functions have been studied: (i) the squared-error loss function as symmetric loss function, (ii) the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…For simulation studies we assume that prior distribution of α follows Gamma (1, 0.5). Sadek and Alharbi (2014) have obtained Bayes estimators based RSS sample for the scale parameter α of Weibull distribution with gamma prior and Jeffreys prior when the shape parameter β is known. We generate SRS, RSS and RSSU samples of sizes n = 2(1)5 for 1000 simulation runs from a Weibull distribution with gamma prior and Jeffreys prior distribution for the scale parameter α when the shape parameter β is known.…”
Section: Simulation Studymentioning
confidence: 99%
See 1 more Smart Citation
“…For simulation studies we assume that prior distribution of α follows Gamma (1, 0.5). Sadek and Alharbi (2014) have obtained Bayes estimators based RSS sample for the scale parameter α of Weibull distribution with gamma prior and Jeffreys prior when the shape parameter β is known. We generate SRS, RSS and RSSU samples of sizes n = 2(1)5 for 1000 simulation runs from a Weibull distribution with gamma prior and Jeffreys prior distribution for the scale parameter α when the shape parameter β is known.…”
Section: Simulation Studymentioning
confidence: 99%
“…Amal Helu et al (2010) have studied Bayes estimators under squared error loss function using sampling schemes namely, RSS and modified ranked set sampling (MRSS) for shape and scale parameter of Weibull distribution and showed the estimators based on RSS and MRSS are better than SRS. Sadek and Alharbi (2014) In recent years, there have been several modifications, proposed to the traditional ranked set sampling method, specifically addressing situations with varying sample sizes. Notable contributions include the works of Bhoj (2001), Al-Odat andAl-Saleh (2001), and Biradar and Santosha (2014).…”
Section: Introductionmentioning
confidence: 99%
“…Ahmed [11] obtained the Bayesian estimators of log-normal distribution based on RSS and SRS using Bayes risk. Sadek et al [12], and Sadek and Alharbi [13] used the asymmetric loss function to obtain the Bayesian estimate of the exponential and Weibull distributions respectively, based on SRS and RSS. Al-Hadhrami and Al-Omari [14] showed that the Bayesian estimation of the mean of normal distribution based on moving extreme ranked set sampling (MERSS) is more efficient than SRS.…”
Section: Introductionmentioning
confidence: 99%